Education and language teaching in the light of recent social and economic needs - Feketéné Silye, Magdolna (Acta Agraria Debreceniensis, 2001)
This paper attempts to describe several general educational potentials that are assumed to facilitate adequate pedagogical response to the recent economic and social paradigm shifts that have resulted in marked changes in the requirements for the labour force on the global job market. The article describes the most powerful pedagogical trends of the 20th century, selectively concentrating on the assessment of their contribution to and share in the preparation of the inevitably forthcoming paradigm shift in education. Topic related issues of language teaching in an academic setting are then discussed, focusing particularily on English for Specific Purposes, followed by a more thorough analysis of the major types of ESP syllabi. This analysis attempts to identify those properties that empower ESP teaching to give a more sophisticated answer (as compared to general language teaching) to issues raised by the appearance of new trends and needs in the global job market. The paper offers conclusions for consideration as to the responsibility of language teachers and strategy makers in higher education, acting in an intercultural environment.